Comparison of different methods in tuning the PID feedback control loop - Goh, Xu Qi (2021)
Among all the control systems, PID controller is the most common control system used in industry. Despite that, choosing a tuning strategy for PID controllers remain a challenge to many practitioners. The purpose of this study is to design and compare different tuning methods of PID temperature controller for a Non-isothermal Continuous Stirred Tank Reactor (CSTR) using MATLAB Simulink. In particular, the study focuses on the performance of three PID tuning method: (i) Ziegler Nichols (Z-N); (ii) Intenal Model Control (IMC); (iii) Integreal of Time-weighted Absolute Error (ITAE) by observing the output temperature response of CSTR. Step change in set point of outlet temperature CSTR from 310K to 350K and step change in inlet disturbance - feed inlet flowrate from 100